The Impact of Full-Day Kindergarten on Maternal Labour Supply - Elizabeth Dhuey; Jessie Lamontagne; Tingting Zhang (Institute of Labor Economics (IZA), 2019)
We examine the impact of offering full-day as a replacement for half-day kindergarten on mothers' labour supply using the rollout of full-day kindergarten in Ontario, Canada. We find no impact on the extensive margin but do find one on the intensive margin. In particular, we find that access to full-day kindergarten increases weekly hours worked and decreases absenteeism for mothers of four-year-olds. We find that this effect is driven by specific sub-groups, namely non-immigrant mothers of only one child with low education levels who live in urban areas.
Keywords: I28; 330; kindergarten; early education; maternal labour supply